Dictionary of energy - Cleveland, Cutler J.; Morris, Christopher G. (Elsevier, 2006)
At a time when the topic of energy prices, resources and environmental impacts are at the forefront of news stories and political discussions, we are pleased to announce the publication of the exciting new Dictionary of Energy. This authoritative resource, called ""an essential reference for energy researchers"" by Mark Jaccard, Director of the Energy and Materials Research Group at Simon Fraser University, covers all aspects of energy and its role in society. * Over 8,000 definitions spanning 40 scientific disciplines* More than 100 'window essays' written.